Reintegration of War‐Fleeing Ukrainians After Their Return to Ukraine - Jauhiainen, Jussi S. (Wiley, 2026)
This article examines the reintegration experiences of Ukrainians who fled the country to the European Union (EU) following Russia's 2022 invasion and subsequently returned while the country was still at war. Employing a mixed-methods approach—including surveys, semi-structured interviews and field observations in Ukraine—the study focuses on the experiences of returnees. By 2025, over 1.2 million Ukrainians had returned from abroad, predominantly women and children from the EU but also from other countries. Return trajectories varied: some returned shortly after displacement, motivated by a strong sense of belonging and sustained ties to Ukraine, while others remained abroad longer and encountered more complex reintegration processes. Most returnees resettled in their original regions, and many found employment quickly amid wartime labour shortages. Although patriotic sentiment intensified during displacement, trust in Ukrainian public institutions remained low. Return was often marked by a decline in life satisfaction and mental health, underlining the psychological challenges of reintegration under war conditions. The study highlights the urgent need for evidence-based reintegration policies that respond to returnees' lived realities that are crucial for Ukraine's recovery, resilience and social cohesion.